VICTIMS OR TERRORISTS? A CRITICAL ANALYSIS OF WESTERN MEDIA DISCOURSE IN THE DEPICTION OF IRAQI REFUGEES (2007-2017) : Received: 15th June 2022; Revised: 28th September 2022, 20th October 2022, 24th October 2022; Accepted: 28th October 2022 - Taher Al-dihaymawee, Doaa (PEOPLE: International Journal of Social Sciences, 2022)
Throughout a long and troubled past Iraq has faced many dogmatic, circumspect, and social plights. Serious problems arising as a cause of these plights have caused many of the population to seek sanctuary and protection in other countries. As a result of this, the increase of refugees now inhabiting Eastern and Western countries becomes a focal point of the media. The way these refugees are depicted and perceived by the public as terrorists or victims in the host and non-host countries is heavily influenced by media reports and as such, they have a crucial role to play. The aim of this paper is to highlight the most significant linguistic choices coupled with the ideological point of view of the participants. To achieve this, the researcher analyses British Broadcasting Corporation (BBC) news reports employing critical discourse analysis. Accordingly, the researcher employs Wodak's (2001; 2009) discourse-historical approach and van Leeuwen's (2008) sociological categories of actor representation approach. The findings of the analysis have revealed that in the Netherlands the Iraqi refugees are portrayed as victims targeted by hostile laws. In the USA they are portrayed as terrorists that threaten society. Under Trump’s administration seven Arab countries including Iraq have been denied entry. Furthermore, the way Iraqi refugees are described by the media is attributed to the use of generic references. Despite the negative representation of Iraqi refugees by the Dutch government, USA policies, and the Iraqi government, the BBC’s media coverage continues to represent them in a neutral light.